Why did God say no to David? (2 Samuel 7). (June 2019) - Goswell, Gregory
The key to discovering why David wants to build a house forYhwh, as well as the reason for the divine refusal, is to be found in a close reading of the opening verse of 2 Samuel 7. This verse is an example of free indirect discourse, namely, the picture of the king's situation (in his house and at rest) is how David viewed the current state of affairs. On that basis, David considered that the time was ripe for such a project, for he was under the misapprehension that he had achieved rest from his enemies (v.1b), but God revealed through Nathan that the time of rest lay in the future (v.11a). Despite differences in wording, the identical explanation for God's embargo on temple-building in the time of David is given in the three passages in 1 Kings and 1 Chronicles that broach the subject.